SEJARAH LAHIRNYA NEGARA ISLAM SEKULER TURKI DAN IDE PEMBAHARUAN MUSTAFA KEMAL - Astaman Astaman; Teguh Murdianto; M. Dahlan. M; Syamzan Syukur (Adisam Publisher, 2025)
The history of the birth of the secular Islamic state of Turkey was a significant transformation in the journey of the Turkish nation, culminating in the dissolution of the Ottoman Empire and the founding of the Republic of Turkey in 1923. This change was spearheaded by Mustafa Kemal Atatürk, a visionary leader who was determined to bring Türkiye towards modernization and secularism. After the collapse of the Ottoman Empire due to defeat in World War I, Mustafa Kemal took advantage of the momentum to replace the religion-based monarchy system with a republic that separated religion from state affairs. Mustafa Kemal's reform ideas included various aspects, such as legal reform with the adoption of European-style civil law, the abolition of the caliphate, and the introduction of the Latin alphabet to replace Arabic letters. Additionally, he promoted secular education, women's emancipation, and economic modernization. This policy aims to eliminate the influence of feudalism and religious dogma which are considered to hinder progress. However, this secularization process is not without challenges, both from conservative groups who oppose drastic changes, and from the international community who question Türkiye's future as a modern country. Despite its pros and cons, Mustafa Kemal's reforms became an important foundation for modern Turkish national identity and an inspiration for reforms in other countries. This research aims to examine the historical course of this transition, the impact of Mustafa Kemal's policies, and its implications for the social, political and cultural dynamics of Türkiye to date.